Adolescents at high risk of obesity show greater striatal response to increased sugar content in milkshakes. Issue 5 (16th May 2018) - Shearrer, Grace E; Stice, Eric; Burger, Kyle S
Abstract: Background: Children of overweight or obese parents are at a high risk of developing obesity. Objective: This study sought to examine the underlying neural factors related to parental obesity risk and the relative impact of sugar and fat when consuming a palatable food, as well as the impact of obesity risk status on brain response to appetizing food images. Design: With the use of functional MRI, the responses of 108 healthy-weight adolescents [mean ± SD body mass index (kg/m 2 ): 20.9 ± 1.9; n  = 53 who were at high risk by virtue of parental obesity status, n = 55 who were low risk] to food stimuli were examined. Stimuli included 4 milkshakes, which systematically varied in sugar and fat content, a calorie-free tasteless solution, and images of appetizing foods and glasses of water. Results: High-risk compared with low-risk adolescents showed greater blood oxygen–dependent response to milkshakes (all variants collapsed) compared with the tasteless solution in the primary gustatory and oral somatosensory cortices ( P -family-wise error rate < 0.05), replicating a previous report. Notably, high-risk adolescents showed greater caudate, gustatory, and oral somatosensory responses to the high-sugar milkshake than to the tasteless solution; however, no effect of risk status was observed in the high-fat milkshake condition. Responses to food images were not related to obesity risk status. Conclusion: Collectively, the data presented here suggest that parental weight status is associated with greater striatal, gustatory, and somatosensory responses to palatable foods—in particular, high-sugar foods—in their adolescent offspring, which theoretically contributes to an increased risk of future overeating. This trial was registered at www.clinicaltrials.gov as NCT01949636.